Interest in Investing in Stocks: The Role of Pocket Money, Family Environment and Investment Knowledge - Putriana, Astia; Alam Sur, Widiya Astuti; Yulika (Universitas Trisakti, 2024)
This research was conducted at the Tanah Laut State Polytechnic for students of accounting study program. This research aims to determine the influence of pocket money, family environment, investment knowledge, on students'interest in investing in shares. This research uses quantitative research where the sample was taken using a purposive sampling technique from 205 students. The data analysis method uses multiple linear regression analysis assisted by SPSS version 26. The results of this study show that pocket money and investment knowledge have a positive and significant effect on students' interest in investing in shares, while the family environment does not significantlyinfluence students' interest in investing in shares. This research is important in opening up insights and becoming a reference for stimulating increased stock investment among college students.